Queen of the darkness - Bishop, Anne (Bishop, Anne. Black jewels series, 2000)
Jaenelle reigns as Queen of Ebon Askavi only as long as she can stave off her enemies, but she cannot do this without help from her consort, Daemon, whose love will help to secure her power, but his love might not be enough.